(untitled) (Nigerian Journal of Technology, 2018)
The treatment of pollution using eco-friendly and sustainable methods is one of the bases of biotechnology. The work reports the use of periwinkle snail shell (PS) as carrier to immobilize Pseudomonas macerans and Bacillus subtilis for the biodegradation of 1-methyl naphthalene in aqueous medium. The biodegradation of 1-methyl naphthalene (500 mg L-1) were monitored after 36 h and 72 h by determining the concentration of carbonic acid (by titrimetric method) following the release of carbon (IV) oxide. The pH as well as the Fourier Transform-infrared (FT-IR)of the metabolites from the bioreactors/reactors were also studied. The pH of all the supernatants in the bioreactors/reactors decreased with time. There was increase in the concentration of H2CO3 due to the biodegradation of 1-methyl naphthalene by immobilized Pseudomonas macerans and Bacillus subtilis on 1.0 g and 2.0 g of PS. However, the use of immobilized Pseudomonas macerans on PS resulted to significant biodegradation of 1-methylnaphthalene (range of 0.61 - 0.81 mg/L H2CO3) compared to degradation alone with PS after 72 h. FTIR of the metabolite at end products show new peaks within 3372- 3268 cm-1 and within 1643-1640cm-1, these bands are attributed to overlapping of hydroxyl (OH) and carbonyl (C=O) stretching in carboxylic acid respectively, this implies that 1-methyl naphthalene got converted to carboxylic acid. Therefore, the use of carbonaceous wastes for localization in order to enhance biodegradation of hydrocarbons can be harnessed for mop-up of oil spills. http://dx.doi.org/10.4314/njt.v37i4.39